Standard Method for Describing an Electronic Patient Record Template: Application of XML to Share Domain Knowledge - Yamazaki, S.; Satomura, Y. (Methods of Information in Medicine, 2000)
A Template Definition Language (TDL) was developed to share knowledge of how to construct an electronic patient record (EPR) template. Based on the extensible markup language XML, TDL has been designed to be independent of EPR platforms or databases. Our research of TDL was conducted through evaluation of the description of various templates in the currently available EPRs and through comparisons with some electronic clinical guidelines. We conclude that TDL is sufficient for the objective but still needs improvement of the algorithm for describing dynamic changes.
Keywords: Knowledge Representation; Computer Based Patient Records; Structured Data Entry; Extensible Markup Language (XML); Protocol Directed Care